Strategi Peningkatan Kompetensi Guru SMK Pelayaran di Indonesia melalui Pelatihan BPSDM Kementerian Perhubungan: Studi pada Kinerja Mengajar, Pemahaman Teknologi, dan Pengembangan Kurikulum - Abadi, Kurniawan (Jurnal Taman Vokasi, 2024)
Professional teachers are an important issue today, the role of teachers in the development of vocational education and learning competencies affects the existence of vocational teacher professionalism. This study analyzes the impact of training provided by BPSDM (Human Resources Education Center) under the Ministry of Transportation on improving the competence of vocational maritime school teachers in Indonesia. The study focuses on three key aspects: teaching performance, technological understanding, and curriculum development. A quantitative method with a path analysis approach was employed, involving 190 vocational maritime teachers as samples. The results show that BPSDM training significantly influences the improvement of teacher competence, particularly in technological understanding and curriculum development. Moreover, school supervision and work motivation play crucial roles in supporting teachers' teaching performance. Continuous training is essential to maintain teacher competence quality in line with international standards, particularly those set by the IMO (International Maritime Organization).